2022
DOI: 10.1037/men0000404
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory study of men’s access to mental health services.

Abstract: Men with mental ill health face multiple barriers to accessing support services. While there is existing work specifically addressing men’s individual help-seeking behaviors, health providers need to better understand broader contexts about access to mental health services. Men seeking help for health-related issues are often stigmatized, and increasingly so when seeking mental health services. This is thought to partly explain the disparities in men’s poor mental health outcomes. The present study aims to imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
1
2
0
Order By: Relevance
“…Although stigma is often a barrier to entry to health services for men, experiences during visits can also determine subsequent help-seeking behaviors (Marcell et al, 2002; Smith et al, 2008a). Seidler et al (2020a) found that dissatisfaction with previous therapy negatively affected perceptions of effectiveness in the future, which aligns with previous evidence outlining multiple characteristics that can affect health service engagement (Scholz et al, 2022) and the client–therapist relationship, which include the following: not the right fit or approach; perceived pressure from the counselor or psychotherapist; lack of trust or uncertainty from the client, the counselor, or psychotherapist acting on assumptions about the client; uncertain expectations from the client about the session; clients not providing enough effort; and scheduling and timing problems (Richards & Bedi, 2015).…”
Section: Discussionsupporting
confidence: 84%
“…Although stigma is often a barrier to entry to health services for men, experiences during visits can also determine subsequent help-seeking behaviors (Marcell et al, 2002; Smith et al, 2008a). Seidler et al (2020a) found that dissatisfaction with previous therapy negatively affected perceptions of effectiveness in the future, which aligns with previous evidence outlining multiple characteristics that can affect health service engagement (Scholz et al, 2022) and the client–therapist relationship, which include the following: not the right fit or approach; perceived pressure from the counselor or psychotherapist; lack of trust or uncertainty from the client, the counselor, or psychotherapist acting on assumptions about the client; uncertain expectations from the client about the session; clients not providing enough effort; and scheduling and timing problems (Richards & Bedi, 2015).…”
Section: Discussionsupporting
confidence: 84%
“…Those involved in the justice system face barriers that make it even more difficult to receive treatment for mental health disorders. For men, who are disproportionately involved in the justice system, gender norms often require them to be self-sufficient, and receiving mental health services is seen as demasculinizing ( Scholz et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Vogel and Heath (2016) advocated embedding measures of masculinity within larger theories of help-seeking (for instance, the theory of reasoned action, by Ajzen & Fishbein, 1980) as a way of facilitating the inclusion of additional contextual factors in analyses. Other authors maintained that the research on men’s mental health has focused on a narrative of “what men do wrong” in relation to their health and illness rather than examining how different men might be willing and able to engage in their own mental health and well-being (Addis et al, 2010; Kiselica & Englar-Carlson, 2010; Scholz et al, 2022; Seidler et al, 2016; Vickery, 2021).…”
mentioning
confidence: 99%